Keterampilan Berfikir Siswa SMP dalam Menyelesaikan Soal Matematika Ditinjau dari Kemampuan Number Sense - Lilik Setyaningsih; Arta Ekayanti (Universitas Syiah Kuala, 2019)
This research aimed to describe the students thinking skills of each number sense category in solving mathematics problems. This study used a qualitative descriptive approach and involved one class of Year 7 students in one of junior high school in Ponorogo, Indonesia. Data collection involved test and non-test. The instruments were number sense ability test and mathematics problems including six cognitive categories. Data analysis included collecting data, reducing data, analyzing data and drawing conclusions. The results showed that students who had low number sense ability were classified as Lower Order Thinking Skill (LOTS) level. In this category, students can only solve mathematics problem involving remembering and understanding categories. While the students with medium number sense ability also identified at LOTS level. In this category, students can only solve the problem involving applying category. Furthermore, the students who had a high number sense ability were classified as Higher Order Thinking Skill (HOTS) level. In this category, students can solve the mathematics problem involving analyzing) and evaluating categories.